Walkable city : how downtown can save America, one step at a time - Speck, Jeff (New York : North Point Press, a division of Farrar, Straus and Giroux, 2013)
Presents a plan for American cities that focuses on making downtowns walkable and less attractive to drivers through smart growth and sustainable design.
A general theory of walkability -- I. Why walkability? : Walking, the urban advantage -- Why Johnny can't walk -- The wrong color green -- II. The ten steps of walkability : The useful walk : Step 1. Put cars in their place ; Step 2. Mix the uses ; Step 3. Get the parking right ; Step 4. Let transit work -- The safe walk : Step 5. Protect the pedestrian ; Step 6. Welcome bikes -- The comfortable walk : Step 7. Shape the spaces ; Step 8. Plant trees -- The interesting walk : Step 9. Make friendly and unique faces ; Step 10. Pick your winners.
Includes bibliographical references : (pages 267-293) and indexes.
Keywords: Urban renewal -- United States; Central business districts -- United States -- Planning; Pedestrian areas -- United States -- Planning; City planning -- United States